Chopin and Polish FOLK - Dahlig-Turek, Ewa (Interdisciplinary Studies in Musicology, 2018)
Although Chopin’s music is continually analysed within the context of its affinities with traditional folk music, no one has any doubt that these are two separate musical worlds, functioning in different contexts and with different participants, although similarly alien to the aesthetic of mass culture. For a present-day listener, used to the global beat, music from beyond popular circulation must be “translated” into a language he/she can understand; this applies to both authentic folk music and the music of the great composer. In the early nineties, when folk music was flourishing in Poland (I extend the term “folk” to all contemporary phenomena of popular music that refer to traditional music), one could hardly have predicted that it would help to revive seemingly doomed authentic traditional music, and especially that it would also turn to Chopin. It is mainly the mazurkas that are arranged. Their performance in a manner stylised on traditional performance practice is intended to prove their essentially “folk” character. The primary factor facilitating their relatively unproblematic transformation is their descendental triple-time rhythms. The celebrations of the bicentenary of the birth of Fryderyk Chopin, with its scholarly and cultural events of various weight geared towards the whole of society, gave rise to further attempts at transferring the great composer’s music from the domain of elite culture to popular culture, which brings one to reflect on the role that folk music might play in the transmission and assimilation of artistic and traditional genres.